2013
DOI: 10.1007/s00406-013-0464-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of variants in DRD2 and GRM3 with motor and cognitive function in first-episode psychosis

Abstract: Background Similar smooth pursuit eye tracking dysfunctions are present across psychotic disorders. They include pursuit initiation and maintenance deficits that implicate different functional brain systems. This candidate gene study examined psychosis-related genotypes regulating dopamine and glutamate neurotransmission in relation to these pursuit deficits. Methods 138 untreated first-episode patients with a psychotic disorder were genotyped for four markers in DRD2 and four markers in GRM3. The magnitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…(Corti et al, 2001). In addition, other clinical studies have reported that rs274622_CC carriers showed a poorer performance in the maintenance of pursuit eye movement than did T-carriers (Lencer et al, 2014), and the addicts carrying the C allele of rs274622 had a shortened duration for transition from first use to dependence in comparison to TT carriers (Jia et al, 2014). Taking these previous findings into consideration, we conceived that the C allele could dysregulate glutamate transmission, which may lead to decreased brain activity in schizophrenia.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…(Corti et al, 2001). In addition, other clinical studies have reported that rs274622_CC carriers showed a poorer performance in the maintenance of pursuit eye movement than did T-carriers (Lencer et al, 2014), and the addicts carrying the C allele of rs274622 had a shortened duration for transition from first use to dependence in comparison to TT carriers (Jia et al, 2014). Taking these previous findings into consideration, we conceived that the C allele could dysregulate glutamate transmission, which may lead to decreased brain activity in schizophrenia.…”
Section: Discussionmentioning
confidence: 81%
“…Fourth, although the effects of each GRM3 SNP on brain activity in the prefrontal cortex are not fully understood (Bishop et al, 2015;Egan et al, 2004;Lencer et al, 2014;Marenco et al, 2006;Tan et al, 2007a;Xia et al, 2012), we divided participants into two SNP subgroups because of small sample size. Genotype group differences without any grouping may clarify the GRM3 effect on brain function.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that genetic variants in the GRM3 gene were associated with schizophrenia-related endophenotypes such as impaired cognition, cortical activation and glutamate markers . Moreover, the association of rs6465084 in GRM3 gene with cognitive processes has been recently reported to drive smooth pursuit eye movements in patients with psychotic disorders, which suggested that alterations in GRM3 coding for the mGluR3 protein may impair pursuit maintenance by compromising higher perceptual and cognitive processes that depend on optimal glutamate signaling in corticocortical circuits (Lencer et al, 2014). These conclusions are consistent with our results, which all provide further supportive evidence that the effects of gene variations on cognitive deficits could be associated with phenotype, despite a mechanistic rationale to explain the association remaining to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we recently demonstrated different associations of sensorimotor and sustained pursuit maintenance impairments with genes regulating dopamine and glutamate systems in psychotic disorders (Lencer et al, 2014). …”
Section: Introductionmentioning
confidence: 99%